Rzeźba Chrystusa z grupy Koronacji Marii z dawnego ołtarza głównego kościoła Wniebowzięcia Najświętszej Marii Panny w Toruniu. Zagadnienie stylu - Dzienis, Monika (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The aim of this work was to recognize the Christ’s sculpture style sources of old – time altar coming from Franciscan St. Mary’s Church in Toruń. This sculpture is particularly important because of its high artistic class and its compound style which has not got any direct analogies on the Teutonic Prussia area so far. The verification of hitherto hypothesis was the beginning for the stylistic – comparative analyses. First of all, Chmarzyński’s analogies between Christ’s figure from Toruń and from altar in Hel Peninsula and also from Erfurt sculptures, so called ‘Severimeister’, pointed by another researcher (Schmid) – were partly essential and they both were taken for the ground in further analyse. However, for closer description of the artistic origin of Christ’s figure was taken the style of painted parts (or segments) from the maternal altar. Consequently, it was noticed the similarity between Christ’s sculpture and the style of Chech’s Master from Vyššiho Brodu (the main point was the comparison of the arrangement of robes). So it can be said that the influence of Czech’s Master on Christ’s sculpture in Toruń is very important and essential. The next point were the searches for analogies in regional sculpture because of the complexity of artistic origin discussed above Christ’s figure. As the result, this article presents other elements of described style – the style of so called Madonna’s on Lions circle (it was popular in Teutonic Prussia) and the other style of sculptures situated on the edge of this workshop circle by other researchers, for instance the altar from Hel and the sculpture from Lidzbark Welski; also – the local work, as the Christ in the Grave sculpture from St. Mary’s Church in Toruń. All the objects, included to the comparative analyses, are simultaneously the indicators in attempt of dating for this described sculpture on about 1370–1380.